2012
DOI: 10.1007/s13644-011-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Differences in Philanthropic Behavior between Christians, Muslims, and Hindus in the Netherlands

Abstract: Using survey data from the Netherlands, we find that Muslims have relatively high levels of religious philanthropic behaviour and relatively low levels of secular philanthropic behaviour, whereas Hindus have relatively low levels of religious philanthropic behaviour and higher levels of secular philanthropic behaviour. Results indicate that the community explanation and the conviction explanation of the relationship between religion and philanthropic behaviour are both valid to some extent when it comes to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Moreover, Carabain & Bekkers (2012) find that Muslim donors in the Netherlands are less likely to engage in secular giving than Protestants and Catholics. Authors argue that philanthropy in Islamic teachings focuses more on supporting fellow Muslims and Islamic institutions, than in Christian teachings.…”
Section: Islam and Donation Behaviormentioning
confidence: 91%
“…Moreover, Carabain & Bekkers (2012) find that Muslim donors in the Netherlands are less likely to engage in secular giving than Protestants and Catholics. Authors argue that philanthropy in Islamic teachings focuses more on supporting fellow Muslims and Islamic institutions, than in Christian teachings.…”
Section: Islam and Donation Behaviormentioning
confidence: 91%
“…Generally, CashWaqf has great potential and a major role in helping higher education institutions in terms of helping students financially as well as institutions in their own right (Carabain & Bekkers, 2011).In addition, Carabain, and Bekkers (2011) showed that Muslims have a relatively high rate of religious giving behavior.The two most critical kind of Islamic charitable giving are Waqf which known as a voluntary charitable gift and zakat also known as a compulsory charity (Idris & Bidin, 2009). b. Religiosity In this study, the researcher determines the level of religiosity able to be one of the predictors to the intention of Waqif to participate in CashWaqf giving scheme.…”
Section: B Theoritical a Cashwaqfmentioning
confidence: 99%
“…The development of a master questionnaire will start with a critical review of the Giving in the Netherlands Panel Survey (GINPS), a high quality survey measuring donations to charitable causes in the Netherlands in an extensive questionnaire module [28,100]. The module produces estimates which are valid (r = .85 between self-reports and archival records of donations received) [28] and reliable [104], also for non-native Dutch citizens with culturally different norms and traditions for giving [105].…”
Section: Ground-breaking Nature Of the Project And Its Innovative Andmentioning
confidence: 99%